Measuring satisfaction with public services - Senior, Nicki (2011)
This study used the 'delivery paradox' (Blaug et al. 2006, p.6) as a catalyst to examine customer satisfaction with the public services. The 'delivery paradox' exists where the rise in the level of delivery improvements does not elicit a corresponding rise in public satisfaction with services (ibid). Expectancy Disconfirmation Theory underpins the measurement of customer satisfaction. However, a review of the literature by MORl (2002) concluded that whilst expectations are known to be shaped by many factors, the role of expectations in affecting satisfaction ratings was confused and over-simplified. This study explored the factors .that influence public service customers' expectations, how expectations changed over time and what effect this had on satisfaction. The study used the Department for Work and Pensions (DWP) as a case study. The sample was drawn from users of Jobcentre Plus. The method used longitudinal interviews over a six-month period, to explore customers' experiences, expectations and satisfaction. Semi-structured telephone interviews with 20 DWP staff members were also carried out to examine how the DWP collects, collates and distributes information on customer satisfaction and complaints. The study does not support the Expectancy Disconfirmation Theory as the dominant model of measurement of customer satisfaction. Although expectations were an important factor, particularly in the initial stages of the relationship with Jobcentre Plus, in isolation they were not the main driver of satisfaction over time. Instead it was an interplay of expectations and orientation towards motherhood or employment that indicated the likelihood of a satisfactory outcome or not. Customers defined themselves in negative, collective terms but demanded a service that reflected individuality. Misinterpretation of service terms, such as 'personal' adviser contributed to dissatisfaction with the service. Personal advisers delivered a service based on negative, collective preconceptions of what the customer desired. The findings indicate redefining service terms in order to eliminate misinterpretation. Furthermore, moving from a traditional expectation based model of customer satisfaction to a process based one, established on negotiated and agreed inputs, outputs and outcomes, is recommended. Overall this work supports and contributes to the development of personalized services within public sector organizations.